Nota dos Editores - Chicarino, Tathiana Senne; de Almeida, Rodrigo Estramanho; Araújo, Rafael de Paula Aguiar (Aurora. Revista de Arte, Mídia e Política, 2014)
Nota dos editores ao número 20 da revista Aurora